Quality Improvement Strategies for State University-Public Sector Agency: Lessons from Student Satisfaction Study - Rini Dwiyani Hadiwidjaja; Arif Imam Suroso; Hermanto Siregar; Illah Sailah (LPPM Universitas Terbuka, 2023)
Purpose – This study aimed to analyze the effect of service quality on student satisfaction as well as formulate quality improvement strategies for State University-Public Service Agency (SU-PSA) in Indonesia. Methodology – The respondents included 290 students from 17 SU-PSA, and the Structural Equation Modeling and Smart PLS were used to analyze data and calculate Community Satisfaction Index (CSI). Results – The results showed that three dimensions (tangibles, responsiveness, and empathy) had a significant effect on student satisfaction at SU-PSA, and two dimensions (reliability and assurance) had no significant impact. Furthermore, tangibles specifically exerted the most significant effect. These results contributed to SU-PSA management in quality improvement strategies and formulating policies for enhancing service completion time for student and addressing complaints, suggestions, and feedback. Improvement quality of educational staff regarding responsiveness and efficiency in serving student could be achieved through training, development, and public awareness efforts. Moreover, CSI provided by SU-PSA in Indonesia fell within the “Good” category. Originality – This study provided valuable insights for enhancing service quality of SU-PSA using the SERVQUAL method, while also accommodating the nine elements of CSI in the context of Higher Education.